Video Coding Technique using MPEG Compression Standards - A. J. Falade; F. J. Olanrewaju (Nigerian Journal of Technological Development, 2013)
Digital video compression technologies have become part of life, in the way visual information is created, communicated and consumed. Some application areas of video compression focused on the problem of optimizing storage space and transmission bandwidth (BW). The two dimensional discrete cosine transform (2-D DCT) is an integral part of video and image compression, which is used in Moving Picture Expert Group (MPEG) encoding standards. Thus, several video compression algorithms had been developed to reduce the data quantity and provide the acceptable quality standard. In the proposed study, the Matlab Simulink Model (MSM) has been used for video coding/compression. The approach is more modern and reduces error resilience image distortion.